Fitness to fly testing in term and ex-preterm babies without bronchopulmonary dysplasia. Issue 3 (23rd July 2011) - Bossley, C J; Cramer, D; Mason, B; Hayward, A; Smyth, J; McKee, A; Biddulph, R; Ogundipe, E; Jaffé, A; Balfour-Lynn, I M
Abstract : Background: During air flight, cabin pressurisation produces an effective fraction of inspired oxygen (FiO2 ) of 0.15. This can cause hypoxia in predisposed individuals, including infants with bronchopulmonary dysplasia (BPD), but the effect on ex-preterm babies without BPD was uncertain. The consequences of feeding a baby during the hypoxia challenge were also unknown. Methods: Ex-preterm (without BPD) and term infants had fitness to fly tests (including a period of feeding) at 3 or 6 months corrected gestational age (CGA) in a body plethysmograph with an FiO2 of 0.15 for 20 min. A 'failed' test was defined as oxygen saturation (SpO2 ) <90% for at least 2 min. Results: 41 term and 30 ex-preterm babies (mean gestational age 39.8 and 33.1 weeks, respectively) exhibited a significant median drop in SpO2 (median −6%, p<0.0001); there was no difference between term versus ex-preterm babies, or 3 versus 6 months. Two term (5%) and two ex-preterm (7%) babies failed the challenge. The SpO2 dropped further during feeding (median −4% in term and −2% in ex-preterm, p<0.0001), with transient desaturation (up to 30 s) <90% seen in 8/36 (22%) term and 9/28 (32%) ex-preterm infants; the ex-preterm babies desaturated more quickly (median 1 vs 3 min, p=0.002). Conclusions: Ex-preterm babies without BPD and who are at least 3 months CGA do not appear to be a particularly at-risk group for air travel, and routine preflight testing is not indicated. Feeding babies in an FiO2 of 0.15 leads to a further fall in SpO2, which is significant but transient.